Meaning in Life on Work Engagement of Defence Officers - Dr Arya Nair (International Journal of Psychosocial Rehabilitation, 2020)
Victor.E. Frankl was the founder of logotherapy based on the triad of principles i.e. the freedom of will, the will to meaning and the meaning of life. According to Frankl will to meaning can be defined as the basic striving of man to find and fulfil meaning and purpose in life. Pleasure rather than being an end of man’s striving is the effect of meaning fulfilment. Both happiness and success are the substitutes for fulfilment and that proves why the pleasure principle and the will to power are mere derivatives of the will to meaning.